Soil Damage Potential Index Based on Weighting Scoring Analysis and Utilization of Geographical Information Systems - Basuki, Basuki; Budiman, Subhan Arif; Mutmainnah, Laily; Rosyady, Muhammad Ghufron (The University of Lampung, 2022)
Indonesia's population in 2021 will increase by 0.92% from 2020. The increasing population demands the fulfillment of food. Land changes and their consequences indicate land damage. The purpose of the study was to assess the soil damage potential index (SDPI) on the slopes of Mount Argopura through terrain analysis and the use of geographic information system technology. The research was carried out on the slopes of Mount Argopura in 2022. The tools used included a clinometer, a GPS, spectrophotometer, AAS, arc GIS 13 and minitab. The materials included administrative maps, soil maps, slope maps, RBI maps, land use maps, rainfall maps. This research is descriptive exploratory with field survey method. The activity is divided into 3 stages, namely pre-survey, field survey, and post-survey. Research parameters include texture, soil thickness, soil type, soil pH, CEC, base saturation, soil drainage, parent material, landform, relief, rainfall, and land use. Based on the results of the study, the SDPI with an area of 22,148.75 ha was in the heavy category 44.12% (9772.28 ha), the medium category was 53.11% (11762.84 ha), and the light category was 2.77% (613.63 ha). Keywords: Geographic Information System, Land Degradation, Mount Argopura, Soil Damage